Freeway safety management: case studies in Italy - De Luca, Mario; Dell’Acqua, Gianluca (Transport, 2012)
Road safety has since become one of the major factors for a description of the state traffic system and crashes are often due to bad made decisions by drivers in environments created by engineers. This study proposes an update of the previous version (Dell’Acqua et al. 2011a) to estimate V 85, for non-conditioned traffic flows on freeways. The databases used in the study come from a series of speed measurements and vehicle ranges on a stretch of freeway using a fixed measuring system. The produced model proved to be very reliable, with the greatest error in the estimation of V 85, being less than 6%. The model obtained was then applied to a stretch of freeway of approximately 20 km. Some significant correlations between DV 85 (variation of V 85 among successive stretches) and DN (the variation in the number of crashes among successive stretches) were found, which may be very useful in the management of safety on roads. In particular the obtained results have highlighted some aspects of motorway traffic. In addition, using the procedure illustrated, it has been possible to identify some particular ‘black spots’ due to the poor design co-ordination of the alignment, positioned between consecutive stretches (for approximately 2 km), with a difference in terms of V 85average greater than 10 km/h. First Published Online: 19 Sep 2012